2020
DOI: 10.1111/jgs.16709
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms and Functional Decline in Alzheimerʼs Disease and Lewy Body Dementia

Abstract: BACKGROUND/OBJECTIVES: Functional status is one of the most important markers of well-being in older adults, but the drivers of functional decline in dementia are not well known. The aim of our work was to study the association of neuropsychiatric symptoms (NPSs) with functional decline over 5 years in newly diagnosed people with Alzheimer´s disease (AD) and Lewy body dementia (LBD). DESIGN: Secondary analysis of the Dementia Study of Western Norway longitudinal cohort study. SETTING: Multicenter study conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
1
20
1
Order By: Relevance
“…Each item was scored from 1 to 4 (Alone = 1, with some help = 2, with a lot of help = 3 and Can Not perform = 4) and then divided over the number of items. We summarized the total mean score of the aforementioned items yearly, over a 5‐year follow‐up 35 36 A higher score indicates a higher level of functional decline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each item was scored from 1 to 4 (Alone = 1, with some help = 2, with a lot of help = 3 and Can Not perform = 4) and then divided over the number of items. We summarized the total mean score of the aforementioned items yearly, over a 5‐year follow‐up 35 36 A higher score indicates a higher level of functional decline.…”
Section: Methodsmentioning
confidence: 99%
“…We summarized the total mean score of the aforementioned items yearly, over a 5-year follow-up. 35,36 A higher score indicates a higher level of functional decline.…”
Section: Functional Decline In Adlmentioning
confidence: 99%
“…We are not in a position to assess REM sleep behavioral disorder as a core feature, as our cohort contained too few patients with REM sleep behavioral disorder and a positive 123I-FP-CIT SPECT result. Another study confirmed such observations, showing that neuropsychiatric symptoms in DLB are more closely related to the extent of functional decline than to any specific symptomology ( Borda et al, 2020 ). Furthermore, our study delivers evidence that 123I-FP-CIT SPECT -positive DLB patients onset more often have a psychiatric-onset (52%), and less often characterized by an MCI-onset of DLB (26%), supporting the relevance of depressive symptoms in suspected DLB patients as the only obvious syndrome at disease onset.…”
Section: Discussionmentioning
confidence: 69%
“…As these studies reveal a mismatch between diagnosis during life and post-mortem, we should be aiming to improve the early diagnosis of DLB. An DLB diagnosis is often impeded by a severe psychiatric presentation ( Borda et al, 2020 ; McKeith et al, 2020 ; Segers et al, 2020 ). Visual hallucinations as a psychiatric symptom are one of DLB’s core clinical features associated with locating Lewy-body pathology ( Sakai et al, 2019 ) and is incompatible with other psychiatric disorders such as schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…BPSD consist of changes in behavior, mood, thoughts, and perception that can be very stressful for the individual and their informal caregivers (family members) [ 2 ]. Furthermore, BPSD are associated with poorer cognitive and everyday functioning, which can increase the risk of early transfer from home to permanent nursing home care and reduce life expectancy [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%